Day-ahead optimal scheduling of integrated energy system with electric heat pump. Issue 1 (February 2020) - Zhang, Nianchu; Wang, Qi; Ni, Ming; Li, Manli; Zhang, Zheng
Abstract: The regional integrated energy system is an effective way to realize energy cascade utilization and improve the flexibility and economy of the load side operation. Combine cooling heating and power (CCHP) system is a typical form of integrated energy systems. However, due to heat-load-based operation mode, the peak modulation capacity of CCHP units and the accommodation of renewable energy are limited. This paper explores methods of increasing the flexibility and economy of the system. An optimal scheduling model is proposed for integrated energy systems containing an electric heat pump, considering heating network characteristics. Simulation results show that the electric heat pump can help the system realize heat-and-power decoupling, improve the flexibility of the system and reduce the operating cost of the system.